Bone mineral density among virologically suppressed Asians older than 50 years old living with and without HIV: A cross-sectional study. - Lalita Wattanachanya; Sarat Sunthornyothin; Tanakorn Apornpong; Hay Mar Su Lwin; Stephen Kerr; Sivaporn Gatechompol; Win Min Han; Thanathip Wichiansan; Sarawut Siwamongsatham; Pairoj Chattranukulchai; Tawatchai Chaiwatanarat; Anchalee Avihingsanon; et al. (PLoS ONE, 2022)
There are limited data regarding bone health in older people living with HIV (PWH), especially those of Asian ethnicity. We aimed to determine whether BMD in well-suppressed HIV-infected men and women aged ≥ 50 years are different from HIV-uninfected controls. In a cross-sectional study, BMD by dual-energy X-ray absorptiometry and calciotropic hormones were measured. A total of 481 participants were consecutively enrolled (209 HIV+ men, 88 HIV- men, 126 HIV+ women and 58 HIV- women). PWH were on average 2.5 years younger [men: 55.0 vs. 57.5 yr; women: 54.0 vs. 58.0 yr] and had lower body mass index (BMI) [men: 23.2 vs. 25.1 kg/m2; women: 23.1 vs. 24.7 kg/m2] compared to the controls. The median duration since HIV diagnosis was 19 (IQR 15-21) years in men and 18 (IQR 15-21) years in women. Three-quarters of PWH had been treated with tenofovir disoproxil fumarate-containing antiretroviral therapy for a median time of 7.4 (IQR 4.5-8.9) years in men and 8.2 (IQR 6.1-10) years in women. In an unadjusted model, HIV+men had significantly lower BMD (g/cm2) at the total hip and femoral neck whereas there was a tend toward lower BMD in HIV+women. After adjusting for age, BMI, and other traditional osteoporotic risk factors, BMD of virologically suppressed older PWH did not differ from participants without HIV (P>0.1). PWH had lower serum 25(OH)D levels but this was not correlated with BMD. In conclusion, BMD in well-suppressed PWH is not different from non-HIV people, therefore, effective control of HIV infection and minimization of other traditional osteoporosis risk factors may help maintain good skeletal health and prevent premature bone loss in Asian PWH. Clinical trial registration: Clinicaltrials.gov # NCT00411983.